Antibody responses of COVID-19 patients according to symptoms and the presence of pneumonia - Faruk Karandere; Ramazan Korkusuz (SERNEV, 2022)
Introduction: The aim of the study was to examine the 30-day total SARS-CoV-2 antibody positivity in patients across a clinical spectrum ranging from asymptomatic to pneumonia.Methods: This prospective cohort study consisted of 51 consecutive patients who were RT-PCR positive and diagnosed COVID-19 pneumonia (Group 1) and 58 consecutive patients who were also RT-PCR positive but were asymptomatic or had mild symptoms (Group 2). On the 30th day from the date of symptom onset, the patients were called for examination and blood samples were taken for the detection of SARS-CoV-2 antibodies.Results: Patients with pneumonia, fever, muscle pain, and loss of taste and smell had significantly higher rates of antibody positivity (p= 0.001, 0.003, 0.030, and 0.018, respectively). Antibody positivity was found to be significantly higher in patients with at least one symptom on admission compared to asymptomatic patients (p = 0.001). While the antibody positivity rate was 96.1% in Group 1 (patients with pneumonia), it was 50% in Group 2 (patients without pneumonia), and 77.7% in patients with at least one symptom on admission compared to 33.3% in asymptomatic patients (p=0.001).Conclusions: Patients with COVID-19 pneumonia have significantly higher disease-specific total antibody positivity rates than patients without pneumonia. Considering the 50% antibody positivity in patients who had COVID-19 infection who were asymptomatic or had symptoms other than pneumonia, the issue of COVID-19 re-infection and immunity is much more important than it appears.